1998
DOI: 10.1128/mcb.18.12.7432
|View full text |Cite
|
Sign up to set email alerts
|

The Leukemic Protein Core Binding Factor β (CBFβ)–Smooth-Muscle Myosin Heavy Chain Sequesters CBFα2 into Cytoskeletal Filaments and Aggregates

Abstract: The fusion gene CBFB-MYH11 is generated by the chromosome 16 inversion associated with acute myeloid leukemias. This gene encodes a chimeric protein involving the core binding factor ␤ (CBF␤) and the smoothmuscle myosin heavy chain (SMMHC). Mouse model studies suggest that this chimeric protein CBF␤-SMMHC dominantly suppresses the function of CBF, a heterodimeric transcription factor composed of DNA binding subunits (CBF␣1 to 3) and a non-DNA binding subunit (CBF␤). This dominant suppression results in the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
126
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 51 publications
10
126
1
Order By: Relevance
“…AML1/ETO is thought to act as a dominant transcriptional repressor that deregulates the expression of RUNX1-responsive cytokine and/or tumor suppressor genes, severely impairing the normal differentiation process. Similarly, a mutated binding partner of RUNX1 identified in leukemias associated with Inv(16)(p13q22), CBF␤-MYH11, acts as a dominant negative inhibitor, although the mechanism of action is not clear (68,87). As we have shown, CBF␤-MYH11 inhibits MHC class I promoter activity in Jurkat T cells (which do not express CIITA constitutively).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…AML1/ETO is thought to act as a dominant transcriptional repressor that deregulates the expression of RUNX1-responsive cytokine and/or tumor suppressor genes, severely impairing the normal differentiation process. Similarly, a mutated binding partner of RUNX1 identified in leukemias associated with Inv(16)(p13q22), CBF␤-MYH11, acts as a dominant negative inhibitor, although the mechanism of action is not clear (68,87). As we have shown, CBF␤-MYH11 inhibits MHC class I promoter activity in Jurkat T cells (which do not express CIITA constitutively).…”
Section: Discussionmentioning
confidence: 90%
“…Aberrations in RUNX1 expression and function have been linked to leukemias, which result as a consequence of somatic chromosomal translocations involving transcription factor genes (43). A number of translocation breakpoint products have been identified that block the normal function of the RUNX1/CBF␤ enhanceosome (27,68,87,88). The (8;21) translocation, found in ϳ10 -12% of acute myeloid leukemias, gives rise to AML1/ETO (new nomenclature: RUNX1-CBF2T1), consisting of the runt domain of RUNX1 in frame with almost the entire ETO gene (77,89).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore thought that the ␣ subunit is synthesized in an inert form, in which the intramolecularly negative regulation of the Runt domain prevents it from interacting with DNA or PEBP2␤. The blocking of Runt domain interactions with PEBP2␤ and with DNA has been indirectly demonstrated by subcellular localization (Lu et al 1995;Adja et al 1998;Kanno et al 1998b) and electrophoretic mobility shift assay (EMSA) , respectively. The modular structure of AML1 as currently understood is shown in Figs 2 and 3.…”
Section: Autoinhibition Of Dna Binding and Heterodimerizationmentioning
confidence: 99%
“…17,19 This notion was based on the observation that, while the Runt homolog by itself was located in the nucleus, the presence of PEBP2␤/CBF␤-SMMHC resulted in retention of the Runt homolog in the cytoplasm. The latter situation appears plausible, since PEBP2␤/CBF␤-SMMHC can still bind the Runt homologs.…”
Section: Introductionmentioning
confidence: 99%
“…15 It must be noted, though, that these results were obtained by transfecting the PEBP2␤/CBF␤-SMMHC expression plasmid into NIH3T3 fibroblasts and REF52 cells or Jurkat cells of the T cell lineage. 17,19 Thus, we were interested to see if sequestration of Runt homologs by PEBP2␤/CBF␤-SMMHC could occur in the cytoplasm of leukemic cells carrying the inversion 16.…”
Section: Introductionmentioning
confidence: 99%